Effect of an extension speech training program based on Chinese idioms in patients with post-stroke non-fluent aphasia: A randomized controlled trial - Sun Pei; Li Weiwei; Zhang Mengqin; He Xiaojun (PLoS ONE, 2023)
Background Chinese idioms have potential to act as preliminary training material in studies on post-stroke aphasia. Objective To explore an extension speech training program that takes Chinese idioms as context and expands them into characters, words, sentences and paragraphs and evaluate the effects of this program in patients with post-stroke non-fluent aphasia. Methods This was a randomized controlled trial. We recruited patients with post-stroke non-fluent aphasia from the Renmin Hospital of Wuhan University from January 2021 to January 2022. Participants were randomly assigned to group I and group II. Patients in group I had treatment with extension speech training based on Chinese idioms, and those in group II had treatment with conventional speech rehabilitation training. The training period in both groups was 40 min daily for 2 weeks. Results A total of 70 patients (group I, n = 34; and group II, n = 36) completed the trial and were analyzed according to protocol. There were no significant differences in baseline values between both groups. After intervention, the scores of oral expression, comprehension, and reading in the Aphasia Battery Of Chinese scale and the scores of the Comprehensive Activities of Daily Living questionnaire significantly improved in both groups (P <0.05), with group I benefiting more (P <0.05). Conclusion This extension speech training program based on Chinese idioms can improve the language function and daily communication ability of the patients with post-stroke non-fluent aphasia. Trial registration Chinese Clinical Trial Registry ChiCTR2000031825.